Conservation biological control in strawberry: effect of different pollen on development, survival, and reproduction of Neoseiulus californicus (Acari: Phytoseiidae) - Gugole Ottaviano, María Fernanda (2015)
Wild vegetation surrounding crops may provide temporary habitat and potential food sources for phytoseiids in different seasons. Monthly vegetation samples of wild plants adjacent to strawberry plants and wild plants in a vegetation strip close to the crop were taken. The frequency of Neoseiulus californicus, Tetranychus urticae and other mites and insects was recorded. In addition, in a laboratory assay, the survival, developmental time and fecundity of females fed on pollen of strawberry and pollen of wild plants where N. californicus was recorded during their flowering, were estimated. Pollen from Urtica urens, Lamium amplexicaule, Convolvulus arvensis, Sonchus oleraceous, Galega officinalis, and Fragaria x ananassa (strawberry) allowed development of N. californicus to adult, but not reproduction. Survival was 70-80 % when fed on pollen from S. oleraceus, G. officinalis and C. arvensis, 80-90 % when fed on pollen from U. urens and F. x ananassa, and more than 90 % when fed on T. urticae and on pollen from L. amplexicaule. In autumn and winter, U. urens, L. amplexicaule and S. oleraceous could promote the persistence of N. californicus when prey density in strawberry is low, offering T. urticae, thrips and pollen. In summer, pollen of C. arvensis and G. officinalis would contribute to the persistence of N. californicus when the strawberry crop is ending and offers scarce food resources. Although the pollen of these plants would not enable the predator population to increase, the presence of these plants in the vicinity of strawberry could contribute to the persistence of N. californicus population and help to limit T. urticae growth when this pest begins to colonize the crop.